Early pulmonary response in rats infected with Trichinella spiralis - Venturiello, Stella Maris (2007)
The migratory stage of Trichinella spiralis, the newborn larva, travels along the pulmonary microvascular system on its way to the striated muscle cells. In the present study, an important inflammatory reaction was observed on days 5 and 14 p.i. in the lungs of infected rats. This inflammation was characterized by a Th2 cell phenotype of an hyperplasic bronchus-associated lymphoid tissue and by goblet cells hyperplasia. Among the inflammatory cells were eosinophils and mast cells scattered over the pulmonary parenchyma. On day 5 p.i. the number of IgE+, CD4+ and CD5+ cells in the bronchus-associated lymphoid tissue were increased and IgE-secreting lung cells were also detected. At the end of the migratory phase of the infection (day 14 p.i.), only IgE+ cells were detected in high numbers and in the bronchoalveolar lavage fluid, an increment in the total IgE levels as well as the presence of IgE and IgA anti-larvae surface were also detected. In cytotoxicity assays, cells from the bronchoalveolar lavage had considerable biological activity since they were able to kill the larvae even in absence of specific antibodies. These results show that the lung is an organ involved in the immune response developed early during a T. spiralis infection and suggest its importance in the protection of the host.